Narratives about Jews among Muslims in Norway: A qualitative interview study - Moe Bjørnbekk, Vibeke (Religious Minorities in the North, 2024)
The interreligious exchange between Islam and Judaism is as old as Islam. Today, the political situation in the Middle East and the situation of Muslims as minorities in Europe constitute important backdrops to the relationship between Muslims and Jews. Based on data from qualitative individual interviews, this book explores narratives about Jews among Muslims in contemporary Norway